Heat, moisture and air transport through clothing textiles. Issue 3 (2nd July 2020) - Maduna, Lebo; Patnaik, Asis
Abstract: The body generates sweat and heat that must be removed from the surface of the skin to the outside environment in order to maintain body temperature. The transfer of sweat, heat and air through the fabric is important for the wearer's comfort. The fabric transports moisture by absorption or wicking processes. Moisture is absorbed by the fabric and when it evaporates it cools the body. Wicking occurs when moisture is transported in between the pores of the fabrics or by capillary action in yarns. Heat transfer involves conduction, convection and radiation and because air movement by convection facilitates the evaporation of sweat, it can make a substantial contribution to causing the body temperature to decrease. Clothing impairs the transfer of heat and moisture from the skin surface to the external environment. Restricting heat transfer to the external environment helps to keep the wearer warm but excessive accumulation of moisture causes clothing to stick to the skin, while the accumulation of heat causes heat stress making the wearer feel uncomfortable. Moisture, heat and air transmission are affected by fibres, fabrics and finishing properties and hydrophilic fibres absorb more moisture than lipophilic fibres. Rapid transportation of sweat and heat helps the body to cool down and the wearer to feel comfortable but protective clothing tends to have lower moisture, heat and air transmission and as a result the accumulation of moisture and heat makes them uncomfortable to wear. Traditional methods of evaluating the effects of moisture, heat and air transmission by clothing use bench-top tests on flat fabric, however, the more-recent use of manikins enables consideration to be taken of body shape as well as fit of the garments.